Low-threshold-current ( 85 mA) of AlGaN-based UV-B laser diode with refractive-index waveguide structure. (3rd September 2021) - Tanaka, Shunya; Ogino, Yuya; Yamada, Kazuki; Ogura, Reo; Teramura, Shohei; Shimokawa, Moe; Ishizuka, Sayaka; Iwayama, Sho; Sato, Kosuke; Miyake, Hideto; Iwaya, Motoaki; Takeuchi, Tetsuya; et al.
Abstract: We report on a refractive-index waveguide AlGaN-based ultraviolet-B band (UV-B) laser diode grown on a sapphire substrate, which achieves a laser oscillation at a low threshold current ( I th ), ∼85 mA. The refractive index waveguide structure in a ridge-type structure is fabricated by a unique method combining dry inductively coupled plasma reactive ion etching and wet etching with tetramethylammonium hydroxide solution. Using this structure, the longitudinal-mode transverse optical confinement is successfully achieved, in which the ridge width is 3 μ m, demonstrating a low I th of UV-B laser diode.